2013
DOI: 10.1021/jf400684n
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Major Phenolic Compounds in Pomegranate Juices by HPLC–DAD–ESI-MS

Abstract: Traditionally, pomegranate (Punica granatum L.) has been consumed as fresh fruit or as pomegranate juice. In this study, the main phenolic compounds of 12 pomegranate varieties and 5 pomegranate clones were determined by HPLC−DAD−ESI-MS. Two chromatographic methods with a fused-core C18 column and a classical HPLC system were developed. Thirteen anthocyanins and fourteen other phenolic compounds were determined in the pomegranate juices. As far as we are concerned, a new flavonol-glycoside, phellatin or its is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 37 publications
4
100
1
Order By: Relevance
“…This knowledge could allow for determination of the optimal harvest time for obtaining the maximum nutritional properties. Other studies on the chemical composition of fruits have also found significant variations in growing locations (Mphahlele et al, 2014;2016), phenolic compounds (Gil et al, 2000;Tzulker et al, 2007;Gómez-Caravaca et al, 2013;Fischer et al, 2013a;Li et al, 2015), sugars (Mphahlele et al, 2016), antioxidant activity (Borochov-Neori et al, 2009;Tehranifar et al, 2010;Zaouay et al, 2012), and mineral composition (Mirdehghan and Rahemi, 2007).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This knowledge could allow for determination of the optimal harvest time for obtaining the maximum nutritional properties. Other studies on the chemical composition of fruits have also found significant variations in growing locations (Mphahlele et al, 2014;2016), phenolic compounds (Gil et al, 2000;Tzulker et al, 2007;Gómez-Caravaca et al, 2013;Fischer et al, 2013a;Li et al, 2015), sugars (Mphahlele et al, 2016), antioxidant activity (Borochov-Neori et al, 2009;Tehranifar et al, 2010;Zaouay et al, 2012), and mineral composition (Mirdehghan and Rahemi, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…The glycosides of the three non-methylated anthocyanidins (delphinidin, cyanidin and pelargonidin) are the most abundant in nature. In this context, pomegranate is a rich source of 3-glucosides and 3,5-diglucosides of delphinidin, cyanidin and pelargonidin (Gómez-Caravaca et al, 2013;Radunic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods were considered for the analysis of the phytoestrogen metabolism by bacteria (Heinonen et al 2001;Cerdá et al 2006;Possemiers et al 2007;Ito et al 2008;Dueñas et al 2009;Bartkiene et al 2011;Elghali et al 2012;Gómez-Caravaca et al 2013). Given the difficulty of finding standards for all isoflavones, lignans, and ellagitannins, as well as the high price of most of them, only standards of the most interesting phytoestrogens were acquired in the present work.…”
Section: Hplc-pad For Phythoestrogens Detectionmentioning
confidence: 99%
“…To date, several chromatographic methods have been developed to detect the presence of phytoestrogens in foods (Heinonen et al 2001;Cerdá et al 2006;Possemiers et al 2007;Ito et al 2008;Bartkiene et al 2011;Elghali et al 2012;Gómez-Caravaca et al 2013). However, none allowed isoflavones, lignans, and ellagitannins to be simultaneously analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…A number of biological activities have been reported on various extracts/constituents of different parts of this plant such as, antibacterial [4] antifungal [5], antiulcer [6] and antitumour [7]. Recently, the antioxidant activity of pomegranate is obvious among in pomegranate fruit, juice and peel [8], this is due to that Pomegranate contains large amounts of polyphenols and flavonoid [9]. Pomegranate peel extracts (PPE) with large quantity of flavonoids and tannins have been shown a high antioxidant activity in several studies [10].…”
Section: Introductionmentioning
confidence: 99%